Picture Game: Vocabulary Dissemination to Elementary Students - Tatik Muflihah (PROCEEDING UMSURABAYA, 2019)
Learning vocabulary is quite different from learning of other aspects of alanguage such as grammar and phonetics that denotes to a learning the rules constantly. Learningvocabulary is a perpetual task for any language learner (Changhong, 2010). This is a descriptivestudy to explore the use of picture game in learning vocabulary to elementary students. The datacollection technique is in the form of observation and documentation in one of state ElementarySchool (SDN) in Surabaya. Picture game is a strategy that make learners enjoy in learning. Thelearners learn new vocabulary and play game as well. Findings of this study suggest theapplication of picture game is valuable to assist students learning vocabulary.Keywords: vocabulary, picture, game